La centralización del clientelismo en México en el sexenio de Andrés Manuel López Obrador - Langston, Joy K. (El Colegio de México A.C., 2025)
This article examines how President Andrés Manuel López Obrador (AMLO) centralized various aspects of clientelism in Mexico during his six-year term in office (2018-2024). During this period, also known as the Fourth Transformation (4T), one sees a profound centralization of intermediation and clientelist exchange from the level of neighborhoods to the federal executive. One of the instruments used to achieve this was the Servants of the Nation, a group of approximately 20,000 federal employees who helped inform and affiliate millions of Mexicans to several federal social programs, making it clear that the president of the nation provided these goods. At the same time, the Servants also undertook (at the behest of their leaders) political and electoral tasks in several elections, supporting Morena and its candidates to remain in government six more years.